Current consensus and controversy on the treatment of male lower urinary tract symptoms/benign prostatic hyperplasia - Chun-Hou Liao; Hann-Chorng Kuo (Tzu Chi Medical Journal)
Lower urinary tract symptoms (LUTS) are highly prevalent in men and increase with age. Because LUTS are common among elderly men, they are usually considered synonymous with benign prostatic hyperplasia (BPH). Drugs should be the first-line treatment for BPH and surgical intervention should be performed only when there are complications or LUTS refractory to medical treatment. In addition to medical treatment, several minimally invasive therapies, such as thermal therapy, prostatic lift, laser evaporation, or laser enucleation techniques have been developed. Recent investigations have also revealed that bladder dysfunction such as detrusor overactivity and detrusor underactivity may also contribute to male LUTS. In the treatment of LUTS suggestive of BPH (LUTS/BPH), the following questions should be considered: Is there an obstruction? Are we treating BPH or LUTS? Can management targeting BPH reduce LUTS? Should patients with LUTS be treated before bladder outlet obstruction is confirmed? What is the role of transurethral resection of the prostate (TURP) nowadays? Will new techniques provide better outcomes than TURP? This article discusses the current consensus and controversies in the treatment of LUTS/BPH.